Deblurring shaken and partially saturated images - Whyte, O; Sivic, J; Zisserman, A (IEEE, 2012)
We address the problem of deblurring images degraded by camera shake blur and saturated or over-exposed pixels. Saturated pixels are a problem for existing non-blind deblurring algorithms because they violate the assumption that the Image formation process is linear, and often cause significant artifacts in deblurred outputs. We propose a for- ward model that includes sensor saturation, and use it to derive a deblurring algorithm properly treating saturated pixels. By using this forward model and reasoning about the causes of artifacts in the deblurred results, we obtain significantly better results than existing deblurring algorithms. Further we propose an efficient approximation of the for- ward model leading to a significant speed-up.